Windwalker - Merrill, Kieth, 1940-; Dubs, Arthur R.; Ballard, Thomas E.; Howard, Trevor, 1916-1988; Ramus, Nick; Remar, James; Hedin, Serene; Jenson, Merrill; Smoot, Reed; Yorgason, Blaine M., 1942-; Pacific International Enterprises; Santa Fe International Corporation; et al. (Fort Mill, SC : Sterling Home Video, 2003)
Lying on his deathbed, the aging Cheyenne Warrior, Windwalker, tells his life's story to his small grandchildren. He recounts his years as a young brave, marriage to beautiful Tashina, the blessing of having twin sons born to them, and his anguish at having Tashina die and one of the babies stolen during a raid by Crow warriors.
Originally produced in 1980 as motion picture.
Based on the novel Windwalker by Blaine Yorgason.
"A Pacific International Enterprises release"--Container.
Bonus features: Original trailers ; Statement from the producer [text feature] ; The Arthur R. Dubs Lifetime Achievement Award (ca. 11 min.) ; Stills gallery ; Cast bios [text feature].
Director of photography, Reed Smoot ; editors, Stephen L. Johnson, Janice Hampton, Peter L. McCrea ; music, Merrill Jenson ; music performed by the The National Philharmonic, London ; set decoration, Rick Barker, Richard Jamison ; costume designer, Yvonne Robertson.
Trevor Howard, Nick Ramus, James Remar, Serene Hedin, Silvana Gallardo, Billy Drago, Dusty Iron Wing McCrea.
Keywords: Cheyenne Indians -- Drama; Crow Indians -- Drama; Indians of North America -- Drama; Reminiscing in old age -- Drama; DVD-Video discs; Action and adventure films; Western films; Film adaptations; Feature films; Fiction films; Video recordings for the hearing impaired